2017
DOI: 10.1186/s11671-017-2269-4
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Properties of Co3O4-Coated TiO2 Powders Prepared by Plasma-Enhanced Atomic Layer Deposition

Abstract: Co3O4-coated commercial TiO2 powders (P25) p-n junction photocatalysts were prepared by plasma-enhanced atomic layer deposition (PEALD) technique. The structure, morphology, bandgap, and photocatalytic properties under ultraviolet light were investigated systematically. Although the deposition of Co3O4 does not change the anatase structure and crystallite size of P25 powders, the ultraviolet photocatalytic activity has been improved evidently. For the Co3O4-coated P25 powders, the trace Co ions exist as Co3O4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…21–1,272). This result indicates that ultrathin ALD Fe 2 O 3 would not affect the crystal structure of TiO 2 , consistent with our previous finding 24 , 55 . In addition, signals related to Fe 2 O 3 were absent.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…21–1,272). This result indicates that ultrathin ALD Fe 2 O 3 would not affect the crystal structure of TiO 2 , consistent with our previous finding 24 , 55 . In addition, signals related to Fe 2 O 3 were absent.…”
Section: Resultssupporting
confidence: 92%
“…High purity nitrogen gas (N 2 , 99.999%) was used as carrier gas at a total flow rate of 750 sccm and a pressure of 6 hPa in our ALD system (Picosun SUNALE™ R-150B). A particular container with porous mesh was used for ALD coating on powders, which has been reported elsewhere 24,55 , as shown in Fig. 1.…”
Section: Methodsmentioning
confidence: 99%
“…The Mott‐Schottky (MS) plots of ZnS and CeO 2 showed a positive slope, it indicated that the ZnS and CeO 2 were n‐type semiconductor [50] . The flat band potential was derived from the intersection of the tangent line and the x‐coordinate of the curve [51–52] . Flat band potentials of ZnS and CeO 2 were 0.3 V and 0.8 V, and they were −0.06 V and −0.56 V relative to the standard hydrogen electrode (NHE) band potentials.…”
Section: Resultsmentioning
confidence: 99%
“…[50] The flat band potential was derived from the intersection of the tangent line and the x-coordinate of the curve. [51][52] Flat band potentials of ZnS and CeO 2 were 0.3 V and 0.8 V, and they were À 0.06 V and À 0.56 V relative to the standard hydrogen electrode (NHE) band potentials. The conduction band potential (E CB ) of n-type semiconductor is more negative about 0.1 V than the flat-band potential.…”
Section: Photocatalytic Mechanism Of Ceo 2 /Zns-cus Compositementioning
confidence: 98%
“…Co3O4 with cubic normal spinel structure can be expressed as AB2O4 where A and B define the magnetic Co 2+ ions in tetrahedral sites and non-magnetic Co 3+ ions in octahedral sites. Co 2+ ions have a high-spin state (S=3/2) while Co 3+ ions possess a low-spin state (S=0) [13][14][15].…”
Section: Introductionmentioning
confidence: 99%